Strategi Kepala Sekolah dalam Mengembangkan Kompetensi Pedagogik Guru di SDN 5 Limboto - Blongkod, Fadlika; Made, Ansar; Nurhayati, Lia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Teaching, broadly defined, constitutes an instructional process, and leaming can occur in diverse environments and at any time. This study employed a descriptive qualitative research design. Data were collected through observation, interviews, and documentation, with the principal of SDN 5 Limboto and the teachers serving as informants. The findings indicate that teachers prepared instructional tools, such as lesson plans and teaching modules, prior to conducting teaching and leaming activities. This preparation demonstrates clear planning in classroom management. Classroom observations revealed that teachers implemented the principal's guidance in the learning process, including adopting varied instructional methods, improving classroom management, and preparing instructional materials more systematically. These results suggest that the principal's strategy extended beyond administrative functions and positively influenced classroom teaching practice.